The membrane glycoprotein M6a endocytic/recycling pathway involves clathrin-mediated endocytosis and affects neuronal synapses - García, Micaela Diana (2017)
Single point mutations or variations in the expression of the gene encoding theneuronal glycoprotein M6a have been associated with psychiatric disorders such as Alzheimer, depression and schizophrenia. In cultured neurons, M6a positivelycontributes to neurite extension, axon guidance, filopodia/spines outgrowth andsynapses formation. Endocytic processes of the neuronal membrane proteins arelinked to differentiation, growth, signalling and neuronal plasticity. However, the precise mechanism in which M6a internalize and recycle back to the neuronal membrane and its roles are unknown. Here we show, by using controlled in vitro assay, that if 40 % of M6a is endocytosed drastically decreased the number of synapses in hippocampal neurons at 15 days in culture. By re-establishing the levels of M6a at cell surface, up to more than 80 %, the number of synapses returned to its normal values. Furthermore, M6a internalization involves cathrin-coated pits probably by the association between the adaptor protein 2, AP-2, with the 251YEDI254 ?tyrosine based? motif located within M6a C-tail. Upon endocytosis, M6a sorted to EEA1 and Rab5 positive endosomes and afterwards can be sorted back to cell surface via Rab11 positive endosomes or conducted to degradation via Rab7 and finally LAMP-1 positive endosomes. Our results demonstrated that the levels of M6a at the cell surface modified the formation/maintenance of the synapses without altering the protein levels ofsynaptophysin and N-methyl-D-aspartate receptor type-1 (NMDA-R1). This novelmechanism might be relevant during the neuronal development, pruning and/or in many mental disorders in which the number of synapses are affected